INDEPENDENSI KEJAKSAAN DALAM SISTEM PERADILAN PIDANA INDONESIA - Ari Wibowo (Istinbath : Jurnal Hukum, 2015)
Lawyer is one of the important institutions in law enforcement, so that in carrying out its functions it should be independent. In Indonesia it is positioned under the executive power where it is considered as vulnerable toward the intervention of executive power in carrying out law enforcement functions. To ensure its independence, the lawyer must be participated in the judicial power. Furthermore, it should be given legitimacy by explicitly stated in the Constitution to ensure the independence of both institutional and functional . The sistem of criminal justice which is applied as the law enforcement system doesn’t not run optimally even become a ruler tool due to its position is subordinated by the executive power. The court Sub-system is structurally and functionally under the authority of the executive, so that its role as law enforcement authorities seems as only serve the interest of ruler. The Sub-systems within the criminal justice system (sub-system investigation, prosecution, and criminal executor) is functionally and institutionally not showed any independence because it is structurally under the executive control. While prosecuting authority (court) has been placed as an independent authority from the executive dominance, either institutional organization, budgets, personnel or kerier systems under one roof (one-roof system) under the Supreme Court. The dependence dominance which is caused as by the dependent institutions, confusion or overlapping law substance and law cultural factors of sub-system of criminal justice executor that tends to be arrogant, ego centric, commercial and serve pragmatic interests beyond the law enforcement purposes.